An Optimality-Based Spatial Explicit Ecohydrological Model at Watershed Scale: Model Description and Test in a Semiarid Grassland Ecosystem - Chen, Lajiao; Hu, Zhidan; Du, Xiaoping; Khan, Mohd Yawar Ali; Li, Xiaojun; Wen, Jie (Frontiers in Environmental Science, 2022)
Optimality principles have been applied in ecohydrological modeling to derive optimal vegetation properties and describe co-evolution states of vegetation and water cycle. Unfortunately, most existing optimality-based models only consider vertical vegetation-soil-water interactions on plot scale, without considering the lateral hydrological processes. This work aims to extend the field-scale Vegetation Optimality-based Model (VOM) to the watershed scale. Lateral hydrological processes are incorporated to VOM, establishing the Distributed Vegetation Optimality Model (DisVOM). The model was tested in the Walnut Gulch watershed, a United States Agricultural Research Service (US-ARS) experimental watershed in southern Arizona. The modelled results demonstrate good consistency with observed temporal and spatial patterns of evapotranspiration (ET) and gross primary productivity (GPP). The spatial variability of the ET and GPP produced by the model is consistent with slope and Topographic Wetness Index (TWI) distribution over the watershed. The DisVOM model has the ability of discriminate the effect of topography on redistribution of precipitation into soil water and the consequent variations in ET and carbon assimilation. The newly developed model descr he spatial variability of ET and GPP produced by the model follow spatial distributions of TWI, SCA, and slope well over the area. The DisVOM model provided a reasonable spatial distribution of ET and GPP and effectively expanded the VOM model to develop optimal canopy patterns based on self-organization of vegetation beyond individual patches.